Telemedicine in Prehospital Acute Stroke Care. Issue 6 (19th March 2019) - Geisler, Frederik; Kunz, Alexander; Winter, Benjamin; Rozanski, Michal; Waldschmidt, Carolin; Weber, Joachim E.; Wendt, Matthias; Zieschang, Katja; Ebinger, Martin; Audebert, Heinrich J.; ,
Abstract : Background: Mobile stroke units (MSUs), equipped with an integrated computed tomography scanner, can shorten time to thrombolytic treatment and may improve outcome in patients with acute ischemic stroke. Original (German) MSUs are staffed by neurologists trained as emergency physicians, but patient assessment and treatment decisions by a remote neurologist may offer an alternative to neurologists aboard MSU. Methods and Results: Remote neurologists examined and assessed emergency patients treated aboard the MSU in Berlin, Germany. Audiovisual quality was rated by the remote neurologist from 1 (excellent) to 6 (insufficient), and duration of video examinations was assessed. We analyzed interrater reliability of diagnoses, scores on the National Institutes of Health Stroke Scale and treatment decisions (intravenous thrombolysis) between the MSU neurologist and the remote neurologist. We included 90 of 103 emergency assessments (13 patients were excluded because of either failed connection, technical problems, clinical worsening during teleconsultation, or missing data in documentation) in this study. The remote neurologist rated audiovisual quality with a median grade for audio quality of 3 (satisfactory) and for video quality of 2 (good). Mean time for completion of teleconsultations was about 19±5 minutes. The interrater reliabilities between the onboard and remote neurologist were high for diagnoses (Cohen's κ=0.86), National Institutes of Health Stroke Scale sum scores (intraclass correlation coefficient, 0.87) and treatment decisions (16 treatment decisions agreed versus 2 disagreed; Cohen's κ=0.93). Conclusions: Remote assessment and treatment decisions of emergency patients are technically feasible with satisfactory audiovisual quality. Agreement on diagnoses, neurological examinations, and treatment decisions between onboard and remote neurologists was high. Abstract : See Editorial by Derry et al